In the presence of the enemy - George, Elizabeth, 1949- (New York : Bantam Books, 1996)
In London, a woman parliamentarian's daughter is kidnaped and a newspaper editor with whom the parliamentarian had an affair receives a call, threatening the girl's life unless he admits paternity. Inspector Lynley suspects the girl is behind it.
Keywords: Great Britain. -- Metropolitan Police Office. -- Criminal Investigation Dept. -- Fiction; Lynley, Thomas (Fictitious character) -- Fiction; Havers, Barbara (Fictitious character) -- Fiction; Women detectives -- England -- Fiction; Kidnapping -- Fiction; Acknowledgment of children -- Fiction; England -- Fiction